Functional Neuroimaging During Asleep DBS Surgery: A Proof of Concept Study - Sammartino, Francesco; Taylor, Paul; Chen, Gang; Reynolds, Richard C.; Glen, Daniel; Krishna, Vibhor (Frontiers in Neurology, 2021)
Object A real-time functional magnetic resonance imaging (fMRI) feedback during ventral intermediate nucleus (VIM) deep brain stimulation (DBS) under general anesthesia (or ‘asleep’ DBS) does not exist. We hypothesized that it was feasible to acquire a reliable and responsive fMRI during asleep VIM DBS surgery. Methods We prospectively enrolled ten consecutive patients who underwent asleep DBS for the treatment of medication-refractory essential tremor. Under general anesthesia, we acquired resting-state functional MRI immediately before and after the cannula insertion. Reliability was determined by a temporal signal-to-noise-ratio greater than 100. Responsiveness was determined based on the fMRI signal change upon insertion of the cannula to the VIM. Results It was feasible to acquire reliable fMRI during asleep DBS surgery. The fMRI signal was responsive to the brain cannula insertion, revealing a reduction in the tremor network's functional connectivity, which did not reach statistical significance in the group analysis. Conclusions It is feasible to acquire a reliable and responsive fMRI signal during asleep DBS. The acquisition steps and the preprocessing pipeline developed in these experiments will be useful for future investigations to develop fMRI-based feedback for asleep DBS surgery.